Criminal jurisdiction of medieval Holy Sees - Balogh, Elemér (Folia theologica et canonica, 2021)
I. The relationship between the church and criminal law; II. Criminal lawsuits in southern German provinces, 1. Augsburg, 2. Eichstätt, 3. Salzburg